New and New-To-You: Transitioning to a New Chair Position - Christopher Barrick (Academic Chairpersons Conference Proceedings, 2020)
Whether you are chairing a department for the first time or starting a chair position at a different institution, your new job will be a challenging transition. This presentation offers practical advice and best practices for adapting to your new position as chair.
Keywords: New; chair; transition; advice; suggestions; mentors; guidance; personal experience; institution